Vulnerable prisoners: Dementia and the impact on prisoners, staff and the correctional setting. Issue 2 (April 2018) - Gaston, Sherryl
Abstract: The aim of this paper is to increase awareness and highlight the need for prisoner's early identification of dementia and recommend support strategies within the Australian correctional setting. The number of older people is increasing within the correctional setting, causing a corresponding increase in the number of prisoners with dementia. These older prisoners are at greater risk of developing cognitive impairment and dementia which increases their vulnerability in the correctional environment including their interactions with both correctional services staff and other prisoners. Correctional settings have not been designed for older prisoners or those with dementia, which poses problems for physical and psychological health. People who have encounters with the criminal justice system are generally in poorer physical and mental health than the general population. Identifying dementia in the early stages provides opportunities to initiate strategies and supports to slow the progression. However being incarcerated increases the likelihood of not being identified with dementia until the later stages of the disease process, which significantly reduces opportunities for early intervention.